Streptomycin as a selective agent to facilitate recovery and isolation of introduced and indigenous Sphingomonas from environmental samples - Karolien Vanbroekhoven; Annemie Ryngaert; Leen Bastiaens; Pierre Wattiau; Marc Vancanneyt; Jean Swings; René De Mot; Dirk Springael (Environmental Microbiology, 2004)
Summary Sphingomonas is an organism of major interest for the degradation of organic contaminants in soils and other environments. A medium based on the aminoglycoside antibiotic streptomycin (Sm) was developed, which, together with the yellow pigmentation of Sphingomonas , facilitated the detection, recovery and quantification of culturable Sphingomonas from soils. All 29 previously described bacterial strains belonging to 17 different Sphingomonas species were able to grow on mineral media containing 200 µg ml −1 streptomycin, showing that the capacity to resist high concentrations of Sm is a common characteristic within Sphingomonas . Incorporation of Sm into the mineral medium led to a significant reduction in the background microbial population and a concomitant 100 times more sensitive detection of Sphingomonas inoculated in non‐sterile soil matrices. The Sm‐containing medium was used to examine a variety of hydrocarbon‐contaminated soils for the presence and biodiversity of Sphingomonas . Incorporation of Sm in the medium led to a significant increase in the number of yellow‐pigmented colonies. Comparison of contaminated and non‐contaminated soils derived from the same site revealed colonization by culturable yellow‐pigmented Sm‐resistant bacteria of the polluted location solely. Both yellow and non‐yellow‐pigmented colonies were purified from plates containing glucose and Sm, and BOX‐polymerase chain reaction (PCR) was used to sort out clonally related strains. Representative strains from the major BOX‐PCR clusters were identified using FAME and partial 16S rRNA gene sequencing. Forty‐eight of 58 Sm‐resistant isolates were identified as Sphingomonas sp. Streptomycin‐resistant Sphingomonas isolates generated BOX‐PCR diversity patterns that were site dependent and represented different species mainly belonging to Sphingomonas subgroups containing species formerly designated as Sphingopyxis and Sphingobium . The ability to degrade phenanthrene was only found in a minority of the Sphingomonas isolates, which all originated from soils containing high phenanthrene concentrations.